2007
DOI: 10.1002/hyp.6899
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic measurement of suspended sediment concentrations: an experimental validation of the approach using kaolin suspensions and reservoir sediments under variable thermal conditions

Abstract: Abstract:Multiphase suspension systems are used extensively in hydrology, biochemistry, and the food industry. Ultrasonic spectroscopy is a rapid, on-line, non-invasive measurement technique for suspension characterization over different particle sizes and a wide range of concentration. Although the properties of kaolin suspensions have been investigated extensively, kaolin ultrasonic attenuation properties at different temperatures and concentrations have not yet been reported. Through experimental validation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
(19 reference statements)
2
2
0
Order By: Relevance
“…Figure 5a shows the relations between SSC and αs in the tank at various frequencies. As predicted by the theory when multiple scattering can be neglected and as observed in numerous other studies (e.g., Hay, 1991; Hunter et al., 2012; Moore et al., 2012; Sung et al., 2008; Rice et al., 2014; Urick, 1948, among others), there is a good linear relation between sound attenuation and sediment concentration (cf. Table 2).…”
Section: Methodssupporting
confidence: 69%
“…Figure 5a shows the relations between SSC and αs in the tank at various frequencies. As predicted by the theory when multiple scattering can be neglected and as observed in numerous other studies (e.g., Hay, 1991; Hunter et al., 2012; Moore et al., 2012; Sung et al., 2008; Rice et al., 2014; Urick, 1948, among others), there is a good linear relation between sound attenuation and sediment concentration (cf. Table 2).…”
Section: Methodssupporting
confidence: 69%
“…Figure 5a shows the relations between SSC and s  in the tank at various frequencies. As predicted by the theory when multiple scattering can be neglected and as observed in numerous other studies (e.g., Hay, 1991;Hunter et al, 2012;Moore et al, 2012;Sung et al, 2008;Rice et al, 2014;Urick, 1948, among others), there is a good linear relation between sound attenuation and sediment concentration (cf. Linear relations between v s and SSC are not as good however (Figure 5b, Table 2).…”
Section: Attenuation and Backscatter Versus Sscsupporting
confidence: 68%
“…Attenuation due to particles has generally been found to vary linearly with concentration at relatively low concentrations with a variety of particle types and fluids (Hay, 1983(Hay, , 1991Hunter et al, 2012a;Richards et al, 1996;Stakutis et al, 1955). In early experiments, Urick (1948) observed a similar linear dependence, as did Greenwood et al (1993) and Sung et al (2008) using kaolin-water suspensions. Greenwood et al concluded that scattering was insignificant in their experiments, since k ) a, and found that attenuation was directly proportional to volume fraction if "there is no interaction between particles."…”
Section: Theorymentioning
confidence: 92%